FRI0304 Treatment of knee osteoarthritis with intra-articular infliximab improves total womac score. High baseline levels of synovial cellularity predict improvement. (23rd January 2014) - Lindsley, H.B.; Schue, J.; Tawfik, O.; Bolce, R.; Smith, D.D.; Hinson, G.; Wick, J.A.
Abstract : Background: Synovial tissue from patients with osteoarthritis (OA) demonstrated synovial inflammation (Benito et al.). We hypothesized that a single intraarticular (IA) injection of an anti-TNF drug would result in decreased inflammatory cell infiltration and ultimately reduce articular injury. Objectives: Evaluate the short-term benefit of IA anti-TNF therapy in knee osteoarthritis. Methods: This study was a single center, 2:1:1 [INF:MP:P] randomization, double-blind, placebo-controlled treatment of knee OA with IA treatments of infliximab (INF) 100 mg, methylprednisolone (MP) 80 mg or saline (P) on Day 0. Subjects (n=16) had to have knee pain and show minimal to moderate osteoarthritic change on plain radiographs. Closed needle synovial biopsies (Bx) were obtained on Days 0 and 28. Total WOMAC was determined at Days 0, 14, 28 and 56. Bivariate associations were investigated using logistic and linear regression. Results: Total WOMAC score improved significantly only for Group INF, comparing baseline to Day 56 (p<0.05) (See Fig). Overall 6 of 16 subjects had high levels of synovial cellularity (level 1-2, scale 0-3) at baseline, 4 of whom were in Group INF. These 4 subjects had the greatest degree of improvement in total WOMAC. Baseline CRP levels (baseline values =0.57-1.21 mg/dl) correlated with total WOMAC scores and did predict improvement (p=0.07). Baseline knee MRI grade (0-5) correlated with baseline total WOMAC but did not predict improvement. Circulating INF levels showed a maximum median concentration at Day 4 (3.70 ug/ml; range 0.56-11.27); two subjects found to have anti-INF antibodies by Day 14 showed reduced levels of INF at Day 14 (median 0.05 ug/ml), compared to the remaining 6 subjects at Day 14 (2.67 ug/ml; range 0.56-3.77). Synovial tissue showed reduction in two markers: CD68 macrophages (3 of 7 Bx INF Group) and CD54 ICAM-1 (2 of 4 Bx MP Group). Flow cytometric studies of PBMCs at Days 0 and 28 showed reduced numbers of INF subjects with TNF-expressing CD20 B cells and CD14 monocytes at Day 28. Conclusions: In this pilot study the Total WOMAC score showed significant improvement by Day 56 (p<0.05) for the INF group. Baseline synovial cellularity and CRP also correlated with improvement. Anti-TNF IA therapy offers promise as symptomatic therapy. References: Benito MJ, et al. Synovial tissue inflammation in early and late osteoarthritis. Ann Rheum Dis 2005;64:1263-7. Disclosure of Interest: H. Lindsley Grant/Research support from: Janssen, J. Schue: None Declared, O. Tawfik: None Declared, R. Bolce: None Declared, D. Smith: None Declared, G. Hinson: None Declared, J. Wick: None Declared